2021
DOI: 10.5937/sejodr7-29735
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of facial landmarks for bone asymmetry in geometric morphometric studies: A review

Abstract: Background Anthropometrical points or landmarks are key for facial shape analysis using geometric morphometrics. In the early 1990s Fred Bookstein created a classification system with landmarks type 1., type 2., type 3. based on anatomical landmark homology. However, thirty years later, a uniform referece index of landmarks that can be used for assessing facial asymmetry still does not exist. The criteria for selecting landmark points are not fully defined, which makes classification of homology and and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A 3D landmark list was taken from Chovalopoulou, Bertsatos, and Papageorgopoulou (2017), as the individual landmarks on this list have been tested for intra‐ and inter‐observer error. The list was then modified as follows: Exclusion of all landmarks of type III, which are at geometric extremes in relation to other landmarks or geometric entities (Bookstein, 1991) Exclusion of landmarks that did not appear in other relevant publications regarding cranial geometric morphometry (an overview can be found in Rupić et al, 2020) Exclusion of landmarks found in areas with high levels of taphonomic alteration (e.g., the zygomatic arch, the nasal spine, and the medial wall of the orbit) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3D landmark list was taken from Chovalopoulou, Bertsatos, and Papageorgopoulou (2017), as the individual landmarks on this list have been tested for intra‐ and inter‐observer error. The list was then modified as follows: Exclusion of all landmarks of type III, which are at geometric extremes in relation to other landmarks or geometric entities (Bookstein, 1991) Exclusion of landmarks that did not appear in other relevant publications regarding cranial geometric morphometry (an overview can be found in Rupić et al, 2020) Exclusion of landmarks found in areas with high levels of taphonomic alteration (e.g., the zygomatic arch, the nasal spine, and the medial wall of the orbit) …”
Section: Methodsmentioning
confidence: 99%
“…Exclusion of landmarks that did not appear in other relevant publications regarding cranial geometric morphometry (an overview can be found in Rupić et al, 2020 )…”
Section: Methodsmentioning
confidence: 99%